À qui appartient-il de déterminer les modes d’intervention auprès des personnes intersexuées ? - Bastien Charlebois, Janik (Nouvelles pratiques sociales, 2016)
Les personnes intersex(ué)es sont au coeur de tensions dans l’orientation des pratiques médicales sur leur corps et la détermination de leur « propre bien ». La volonté d’autodétermination relayée par les acteurs sociaux politisés et les critiques qu’ils formulent à l’endroit des médecins se heurtent au déficit de crédibilité que celle-ci leur accorde. En isolant certains des motifs les plus solides du maintien de la primauté médicale sur l’orientation des pratiques, nous relevons les arguments développés par la communauté intersexe pour y répondre. Cette réflexion est menée à partir des perspectives philosophiques de Young sur l’autodétermination et du concept d’injustice épistémique de Fricker.
http://www.erudit.org/fr/revues/nps/2016-v28-n1-nps02990/1039174ar/
Keywords: approches et analyses; autodétermination; corps; cours; discipline; fem1000; histoire et politique; identités LGBTQIA2+; lit4700; militance; médecine; personnes intersexes; point de vue situé; premier cycle; ressource en ligne; sciences; thématiques

Glaciers, gender, and science: A feminist glaciology framework for global environmental change research - Carey, Mark; Jackson, M.; Antonello, Alessandro; Rushing, Jaclyn (Progress in Human Geography, 2016)
Glaciers are key icons of climate change and global environmental change. However, the relationships among gender, science, and glaciers – particularly related to epistemological questions about the production of glaciological knowledge – remain understudied. This paper thus proposes a feminist glaciology framework with four key components: 1) knowledge producers; (2) gendered science and knowledge; (3) systems of scientific domination; and (4) alternative representations of glaciers. Merging feminist postcolonial science studies and feminist political ecology, the feminist glaciology framework generates robust analysis of gender, power, and epistemologies in dynamic social-ecological systems, thereby leading to more just and equitable science and human-ice interactions.
Keywords: approches et analyses; discipline; environnement; glaciologie; histoire et politique; intersectionnalité; point de vue situé; projet charge mentale; sciences; sciences de la terre; thématiques; études postcoloniales

Disability studies after the ontological turn: a return to the material world and material bodies without a return to essentialism - Feely, Michael (Disability & Society, 2016)
Over recent decades, poststructuralist theories have allowed critical disability scholars to challenge essentialist understandings of the human species and to contest discourses which divide humans into ‘normal’/‘impaired’ subjects with respect to a wide – and ever expanding – range of corporeal and cognitive traits. For critics, however, these theories are deeply flawed. By focusing primarily on language, poststructuralism shifts our critical attention away from the often harsh material realities of life for disabled people. This has led some to turn to critical realism and to effectively re-essentialise impairment. In this article, I wish to consider an alternative approach. I suggest that the recent ‘ontological turn’ in social theory has seen the emergence of new-materialist approaches – including Deleuze and Guattari’s ontology of assemblage and methodology of assemblage analysis – which allow us to consider disability as a material phenomenon without a return to essentialism.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; approches et analyses; corps; cours; discipline; féminisme matérialiste; histoire et politique; humaines; ontologie; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; thématiques; études critiques du handicap